Translation as an aid to ELT: Using an English-Spanish parallel corpus (P-ACTRES) to study English both and its Spanish counterparts. - Labrador, Belen (Digital Scholarship in the Humanities, 2016)
The present article reports on a corpus-based study that explores the relationship between English dual quantifier both and its Spanish equivalents, especially dual quantifier ambos/as, which is perceived as being functionally similar. The aim of this research is to shed some light on the causes of Spanish students' underuse of both in their writing by analyzing and classifying the translation solutions for each different use of both and by comparing the use of both and its Spanish counterparts in fictional discourse and in non-fictional discourse to search for any possible cross-register differences. A parallel English-Spanish corpus, P-ACTRES, an ad hoc corpus of contemporary English texts and their corresponding translations into Spanish, has been used for the purpose of this study.